Empleamos estrategias para resolución de problemas de cantidad - Hidalgo Dioses, Jhon Erwin (2019)
The session entitled "We use strategies for quantity problem solving" is designed for the fourth grade of Primary Education, was developed in the area of Mathematics. In the elaboration of the session, work has been carried out with the pedagogical and didactic processes of the area of mathematics to promote meaningful learning. The strategies used were designed to promote active and meaningful participation of all students. It is intended at all times to arouse the student's interest and motivation for mathematics, since it is a very important and valuable area. The Introduction is geared towards class planning, the performance to be evaluated, the learning evidence and the evaluation tool to be used. The second part develops the Theoretical Sustainwhere where the conceptual definitions of the main variables of the subject to be discussed are exposed, in order to explain what is stated in the present work in a simple and on a basis that supports it. Finally, the third part is dedicated to Pedagogical Sustenance, the foundation of the Mathematics Area according to the new Curriculum Framework, considering the profile of the egress that the student must achieve at the completion of the Regular Basic Education and the approaches that orient the Area in mention. In addition to the pedagogical and didactic processes of the área and the techniques and evaluation tools.